2017
DOI: 10.1016/j.intimp.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing miR-132 expression by aryl hydrocarbon receptor attenuates tumorigenesis associated with chronic colitis

Abstract: Our findings identify miR-132 as a new molecule implicated in CAC pathogenesis, and reveal that miR-132 mediates the ameliorating effects of TCDD on CAC, suggesting miR-132 as a promising therapeutic candidate to control autoimmune inflammation and tumorigenesis in CAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…AhR and its effects on the NLRP3 inflammasome and colitis have been predominantly studied using wild-type (AhR +/+ ), AhR knockout (AhR −/− ) and heterozygous (AhR −/+ ) mouse models that have been chemically induced with intestinal inflammation; by using 2,4,6-trinitrobenzene sulphonic acid (TNBS) or dextran sulphate sodium (DSS), and CAC; by using azoxymethane (AOM or AOM/DSS) [70]. Several studies have determined that AhR exhibits protective effects during intestinal inflammation; with TCDD-treated and FICZ-treated mice ameliorating colitis severity, which were determined from corrected weight loss, reduced colitis symptoms and recover periods [159][160][161][162][163]. These reversed colitis effects were due to a change in their cytokine environment, with AhR-activated mice having a reduction in the expression of pro-inflammatory mediators; such as IL-6, IL-12, IL-17, IFN-c, MCP-1, exotaxin-1 and TNF-α, but an increase in IL-22 and TGF-β [159,162,163].…”
Section: Role Of Mouse Models In the Investigation Of Ahr In Maintainmentioning
confidence: 99%
See 1 more Smart Citation
“…AhR and its effects on the NLRP3 inflammasome and colitis have been predominantly studied using wild-type (AhR +/+ ), AhR knockout (AhR −/− ) and heterozygous (AhR −/+ ) mouse models that have been chemically induced with intestinal inflammation; by using 2,4,6-trinitrobenzene sulphonic acid (TNBS) or dextran sulphate sodium (DSS), and CAC; by using azoxymethane (AOM or AOM/DSS) [70]. Several studies have determined that AhR exhibits protective effects during intestinal inflammation; with TCDD-treated and FICZ-treated mice ameliorating colitis severity, which were determined from corrected weight loss, reduced colitis symptoms and recover periods [159][160][161][162][163]. These reversed colitis effects were due to a change in their cytokine environment, with AhR-activated mice having a reduction in the expression of pro-inflammatory mediators; such as IL-6, IL-12, IL-17, IFN-c, MCP-1, exotaxin-1 and TNF-α, but an increase in IL-22 and TGF-β [159,162,163].…”
Section: Role Of Mouse Models In the Investigation Of Ahr In Maintainmentioning
confidence: 99%
“…Several studies have determined that AhR exhibits protective effects during intestinal inflammation; with TCDD-treated and FICZ-treated mice ameliorating colitis severity, which were determined from corrected weight loss, reduced colitis symptoms and recover periods [159][160][161][162][163]. These reversed colitis effects were due to a change in their cytokine environment, with AhR-activated mice having a reduction in the expression of pro-inflammatory mediators; such as IL-6, IL-12, IL-17, IFN-c, MCP-1, exotaxin-1 and TNF-α, but an increase in IL-22 and TGF-β [159,162,163]. The results from Monteleone et al supports this notion with FICZ-treated TNBS-induced mice showing reversed colitis symptoms while also showing that colitis symptoms were enhanced when the mice were treated with AhR antagonists [164].…”
Section: Role Of Mouse Models In the Investigation Of Ahr In Maintainmentioning
confidence: 99%
“…AHR-mediated carcinogenesis with the disruption of eicosanoid homeostasis as reviewed recently [30], is involved in breast cancer [328,329], colitis associated colon cancer through miR-132 expression after AHR activation by TCDD [330]. B[a]P induces AHR-dependent IL-10 increase with chronic inflammation [331] and AHR is involved in inflammatory fibrosis of the pancreas [332] and the liver [333].…”
Section: Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%
“…Within these regulatory networks, microRNAs (miRs) can interact with downstream target genes, some of which have been linked to cancer progression (9). A recent study demonstrated that increased levels of miR-132 by aryl hydrocarbon receptor attenuate tumorigenesis associated with chronic colitis (10). Furthermore, it was revealed that miR-141 was involved in the pathogenesis of ulcerative colitis by targeting C-X-C motif chemokine ligand 5 (11).…”
Section: Introductionmentioning
confidence: 99%